2009
DOI: 10.1111/j.1399-302x.2009.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive increase of human papillomavirus carriage rates in potentially malignant and malignant oral disorders with increasing malignant potential

Abstract: HPVs may be involved in the development or progression of not only OSCC but also of potentially malignant oral lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 31 publications
3
67
1
Order By: Relevance
“…Only data generated from primary squamous cell carcinomas (SCC) were extracted, and we excluded reports if: (1) the detection methods were not well-detailed, and/or (2) HPV data could not be extracted per anatomic site. We took care to avoid tallying overlapping patient cohorts [2][3][4][5][6][7][8][9][10][11][12][13]. The final extracted data included: county, year of publication, anatomical site, HPV type, detection method of including primers, and summary of findings for cancers, patient controls, benign lesions, potentially premalignant lesions, and premalignant lesions, when available.…”
Section: Methodsmentioning
confidence: 99%
“…Only data generated from primary squamous cell carcinomas (SCC) were extracted, and we excluded reports if: (1) the detection methods were not well-detailed, and/or (2) HPV data could not be extracted per anatomic site. We took care to avoid tallying overlapping patient cohorts [2][3][4][5][6][7][8][9][10][11][12][13]. The final extracted data included: county, year of publication, anatomical site, HPV type, detection method of including primers, and summary of findings for cancers, patient controls, benign lesions, potentially premalignant lesions, and premalignant lesions, when available.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple HPV types were present in 17 of 30 (56.7%) specimens and 2 specimens contained HPV-16, -18 and other types. Using real-time PCR analysis, Szarka et al demonstrated that the HPV prevalence increased gradually with the severity of the lesions (32.8, 40.9 and 47.7% in oral lichen planus (OLP), oral leukoplakia (OL) and OSCC, respectively) (Szarka et al, 2009). Similarly, the average HPV copy numbers by the real-time PCR were 5.2 X 10 2 (range: 10-840), 6.8 X 10 3 (range 10-51,000), 7.2 X 10 3 (range 10-27,000) and 2.4 X 10 5 (range 90-130,000) per µg of total DNA in oral controls, OLP, OL and OSCC patients, respectively (18).…”
Section: Enumeration Of Viral Copy Number By Real-time Pcrmentioning
confidence: 99%
“…In an Italian study it was estimated that there is a 7.8-times higher risk of HPV in oral premalignant lesions than in normal mucosa (7). A study from Hungary reported 32.8% of HPV-positive OLP lesions (3). Th e same group later reported percentage of HPV-positive OLP to be 19.7% (8).…”
mentioning
confidence: 91%
“…During the last decades, several studies have suggested that human papillomaviruses (HPVs) are involved in the development of premalignant and malignant lesions (2). Th e causal role of HPV has been reported for OLP and oral squamous cell carcinoma, but there are wide variations in disease prevalence with regard to diff erent geographic populations (3). Th e aim of this study was to determine the prevalence of HPV on the mucosa in patients with OLP and compare it with healthy mucosa.…”
mentioning
confidence: 99%